ACQUIRED IMMUNITY TO CANDIDIASIS IN MICE - Hasenclever, H. F. (1963)
Hasenclever, H. F. (National Institute of Allergy and Infectious Diseases, Bethesda, Md.) and William O. Mitchell. Acquired immunity to candidiasis in mice. J. Bacteriol. 86:401–406. 1963.—Some protection to chronic candidiasis in mice was produced by sublethal intraperitoneal infection with Candida albicans and by the injection in incomplete Freund's adjuvant of nonviable Coccidioides immitis spherule fragments. Other pathogenic or nonpathogenic fungi produced little or no protection. Salmonella enteritidis lipopolysaccharide, known to protect mice against the acute toxic manifestations of C. albicans, had no effect upon chronic candidiasis. A factor active in vitro against the growth of C. albicans was shown to be in the serum of resistant mice.